Effect of irradiation and thermo-induced processes on reactor in vessel elements during long-term operation - Breslavsky, Dmytro; Tatarinova, Oksana; Kalchenko, Olexandr; Tolstolutska, Galyna (National Science Center "Kharkov Institute of Physics and Technology", 2022)
A method for determining the effect of inhomogeneous temperature distribution, irradiation damage, irradiation swelling, irradiation creep of the material on the long-term strength of reactor in vessel internals and their deformation has been developed. The deformed state of the WWER type nuclear reactor baffle was determined. Constitutive equations taking into account the hidden damage of the material are proposed. According to the results of computer simulations, the strain fields of the section of the baffle during its operation for 60 years were analyzed, the place of possible occurrence of a macroscopic defect was determined.

Розроблено метод визначення впливу неоднорідного розподілу температури, радіаційного пошкодження, об'ємного радіаційного розпухання, радіаційної повзучості матеріалу на довготривалу міцність внутрішньокорпусних елементів та їх формозмінення. Визначено деформований стан вигородки ядерного реактору типу ВВЕР. Запропоновано рівняння стану, що враховують приховану пошкоджуваність матеріалу. За отриманими результатами комп’ютерного моделювання проаналізовано поля деформацій перерізу вигородки при її експлуатації протягом 60 років, встановлене місце можливого виникнення макроскопічного дефекту.
Keywords: method for determining the effect of inhomogeneous temperature distribution; irradiation damage; reactor in-vessel internals; deformed state; irradiation swelling; irradiation creep; метод визначення впливу неоднорідного розподілу температури; радіаційне пошкодження; внутрішні конструкції реактора в корпусі; деформований стан; радіаційне набухання; радіаційна повзучість